PERSPEKTIF ORANG TUA TENTANG KESIAPAN ANAK USIA DINI MEMASUKI JENJANG SEKOLAH DASAR - Amalia, Annisa; Miranda, Dian Miranda; Lukmanulhakim, Lukmanulhakim; R, Marmawi; Yuniarni, Desni; Linarsih, Andini (Universitas Tanjungpura, 2023)
This research aims to reveal the prespective of parents regarding the meaning of school readiness to enter elementary school from the early childhood education stage. Parents' perceptions of school readiness are related to children's early education experience, which can support optimizing their readiness to enter elementary school. The method of this research is a phenomenological study that reveals the perceptions of parents who have children in the age range of 5-6 years that have not entered the elementary education stage. Research data collection is through interviews. The technique used for processing data is IPA (Interpretative Phenomenological Analysis) techniques. This data processing technique is implemented through six (6) stages, which consist of 1) Reading and re-reading; 2) Initial noting; 3) Developing Emergent themes; 4) Searching for connections across emergent themes; 5) Moving the next cases; and 6) Looking for patterns across cases. Parents' perceptions show that young children ready to enter primary school can read, write, count, be independent, and have mental readiness. Parents see that there will be changes in demands between PAUD and elementary school levels, so children need to be prepared for these changes. Meanwhile, parents' views on schools and teachers in preparing children show trust and hope that schools can play a good role.